Multitarget, selective compound design yields potent inhibitors of a kinetoplastid pteridine reductase 1 - Pöhner, Ina; Quotadamo, Antonio; Panecka-Hofman, Joanna; Luciani, Rosaria; Santucci, Matteo; Linciano, Pasquale; Landi, Giacomo; Di Pisa, Flavio; Dello Iacono, Lucia; Pozzi, Cecilia; Mangani, Stefano; Gul, Sheraz; et al. (Journal of medicinal chemistry, 2022)
The optimization of compounds with multiple targets is a diﬃcult multidimensional problem in the drug discovery cycle. Here, we present a systematic, multidisciplinary approach to the development of selective antiparasitic compounds. Computational fragment-based design of novel pteridine derivatives along with iterations of crystallographic structure determination allowed for the derivation of a structure−activity relationship for multitarget inhibition. The approach yielded compounds showing apparent picomolar inhibition of T. brucei pteridine reductase 1 (PTR1), nanomolar inhibition of L. major PTR1, and selective submicromolar inhibition of parasite dihydrofolate reductase (DHFR) versus human DHFR. Moreover, by combining design for polypharmacology with a property-based on-parasite optimization, we found three compounds that exhibited micromolar EC50 values against T. brucei brucei while retaining their target inhibition. Our results provide a basis for the further development of pteridine-based compounds, and we expect our multitarget approach to be generally applicable to the design and optimization of anti-infective agents.
Gesehen am 15.09.2022